PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP KEDISIPLINAN PESERTA DIDIK - Sari, Ratna; wardi, Suhro; Hasani, Syarief (Prodi PAI IAILM Suryalaya, 2021)
This research aims to find out the influence of scouting extracurricular activities on the discipline of learners at SMPI Serba Bakti. The method used in this study is a deskrptif method through quantitative approaches that are research that seeks to reveal the current circumstances or conditions by considering past circumstances through the processing of numbers obtained from research. Based on the results of data management, it was obtained that the influence of extracurricular activities on the discipline of learners at SMPI Serba Bakti has a significant positive influence with enough categories. Proven rs = 0.48 is at intervals of 0.40 – 0.60 and thitung 2,500 ≥ 2,080. So the influence of the influence of extracurricular activities on the discipline of learners in SMPI Serba Bakti has a percentage of 23% and 77% of other factors that affect discipline such as peers, family and so on.